Vertebral Erosion Secondary to Aortic Aneurysm - Zakaria Toufga; Fadma Aoujil; Nabil Moatassim Billah; Ittimad Nassar (Case Reports in Radiology)
We report the case of a patient who presented for back pain with paresthesia, and the CT showed vertebral lysis of aneurysmal origin. The aneurysm of the thoracic aorta compresses the anterior surface of the dorsal vertebrae and by mechanical effect is responsible for the destruction of the opposite bone. The knowledge of this cause is very important considering the frequency of other tumoral and infectious causes of this affection.